2017
DOI: 10.2807/1560-7917.es.2017.22.41.16-00715
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of diagnosis criteria in patients with suspected diagnosis of sporadic Creutzfeldt-Jakob disease and detection of 14-3-3 protein, France, 1992 to 2009

Abstract: International audienceDiagnostic criteria of Creutzfeldt–Jakob disease (CJD), a rare and fatal transmissible nervous system disease with public health implications, are determined by clinical data, electroencephalogram (EEG), detection of 14-3-3 protein in cerebrospinal fluid (CSF), brain magnetic resonance imaging and prion protein gene examination. The specificity of protein 14-3-3 has been questioned. We reviewed data from 1,572 autopsied patients collected over an 18-year period (1992–2009) and assessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…These findings are similar to findings by Torres et al (2012) where 14-3-3 protein levels were inconsistent in longitudinal samples and did not track with advancing disease in CJD patients [43]. Furthermore, use of 14-3-3 detection in the diagnosis of CJD has led to an increase in over diagnosis of sporadic CJD and misdiagnosis of potentially treatable diseases [46,47]. Our data indicates a lack of prognostic utility for 14-3-3 and NSE for prion infection and questions the utility of these biomarkers for clinical diagnosis in the context of improved imaging and development of direct detection of PrP CJD by RT QuIC.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are similar to findings by Torres et al (2012) where 14-3-3 protein levels were inconsistent in longitudinal samples and did not track with advancing disease in CJD patients [43]. Furthermore, use of 14-3-3 detection in the diagnosis of CJD has led to an increase in over diagnosis of sporadic CJD and misdiagnosis of potentially treatable diseases [46,47]. Our data indicates a lack of prognostic utility for 14-3-3 and NSE for prion infection and questions the utility of these biomarkers for clinical diagnosis in the context of improved imaging and development of direct detection of PrP CJD by RT QuIC.…”
Section: Discussionsupporting
confidence: 86%
“…However, the specificity of this test has been questioned. In one study, a false positive rate of approximately 30% was found in a population with 14-3-3 protein detected in the CSF who also met diagnostic criteria for probable sCJD 4. Only 59% of this population were found to have sCJD and, interestingly, none were found to have CBD pathology 4.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a false positive rate of approximately 30% was found in a population with 14-3-3 protein detected in the CSF who also met diagnostic criteria for probable sCJD 4. Only 59% of this population were found to have sCJD and, interestingly, none were found to have CBD pathology 4. A diagnostic test such real-time quaking induced conversion (RT-QuIC), with a similar sensitivity to 14-3-3 CSF analysis but a specificity rate of 98%–100%5 6 would have been a more useful test for the diagnosis of CJD before the patient’s death.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar puncture and extraction of CSF is a usual procedure in patients showing neurological signs and especially in those presenting rapidly progressive dementias. Since the quantification of 14-3-3 protein levels is one of the standardized diagnostic criteria [91], this body fluid is available for most of the patients suspected of a TSE. Since the first human CSF-adapted RT-QuIC was reported in 2011, in which from 48 CSF samples of sCJD, iCJD and from other neurodegenerative pathologies they achieved about 80% sensitivity and 100% specificity [92], improvements mainly in the recombinant PrP used as substrate have allowed to increase the sensitivity and to screen for other TSEs apart from sCJD and iCJD [42,93].…”
Section: Prp Sc In Csf In Human Prion Diseasesmentioning
confidence: 99%